2016
DOI: 10.1016/j.celrep.2016.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Control of Smc Coiled Coil Architecture by the ATPase Heads Facilitates Targeting to Chromosomal ParB/parS and Release onto Flanking DNA

Abstract: SummarySmc/ScpAB promotes chromosome segregation in prokaryotes, presumably by compacting and resolving nascent sister chromosomes. The underlying mechanisms, however, are poorly understood. Here, we investigate the role of the Smc ATPase activity in the recruitment of Smc/ScpAB to the Bacillus subtilis chromosome. We demonstrate that targeting of Smc/ScpAB to ParB/parS loading sites is strictly dependent on engagement of Smc head domains and relies on an open organization of the Smc coiled coils. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
172
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(192 citation statements)
references
References 47 publications
20
172
0
Order By: Relevance
“…Interestingly, this localization phenotype is similar to the EQ mutant, which in contrast to the Mini-Smc proteins is blocked in ATP hydrolysis (Hirano and Hirano, 2004, Minnen et al., 2016) (Figures 4A and S4A). We confirmed these findings by ChIP coupled to quantitative PCR (qPCR), which also showed that the extent of redistribution correlated well with the ability of Mini-Smc proteins to support fast growth (Figure S4B).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, this localization phenotype is similar to the EQ mutant, which in contrast to the Mini-Smc proteins is blocked in ATP hydrolysis (Hirano and Hirano, 2004, Minnen et al., 2016) (Figures 4A and S4A). We confirmed these findings by ChIP coupled to quantitative PCR (qPCR), which also showed that the extent of redistribution correlated well with the ability of Mini-Smc proteins to support fast growth (Figure S4B).…”
Section: Resultsmentioning
confidence: 71%
“…We performed site-specific cysteine crosslinking experiments in vivo and found that dimerization at the hinge domain was normal in the six tested Mini-Smc proteins (Figures 3A and S3B). Likewise, the Smc head domains engaged robustly in the presence of a mutation blocking ATP hydrolysis (E1118Q [EQ]), whereas head engagement was hardly detectable in the absence of this mutation, as observed with full-length Smc (Minnen et al., 2016) (Figures 3B and S3C; see Figure S3A for an overview of the SMC ATP hydrolysis cycle). Curiously, the efficiency of head engagement in Smc(EQ) proteins increased somewhat as the coiled coil was shortened (Figures 3B and S3D), consistent with our previous proposition that the formation of a rod by close juxtaposition of the two Smc coiled coils hinders head engagement (Minnen et al., 2016, Soh et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…ScpAB have been shown to convert Smc—that binds DNA via coiled coil opening at hinge domains (loosely-DNA bound Smc)—to stably DNA-bound Smc rings, which involves head interactions of Smc (62). We show that ∼60% of ScpA monomers (about 50 monomers per cell) are statically positioned, dependent on the presence of Smc, and therefore must be bound to Smc dimers at the SMC clusters, while 40% of ScpA are diffusing through the cell.…”
Section: Discussionmentioning
confidence: 99%
“…subtilis and Streptococcus pneumoniae , where the ParB- parS complex recruits SMC to the oriC region, thereby allowing correct chromosome segregation [1416]. This recruitment is thought to depend on ParB ability to bridge DNA, a phenomenon previously described as “spreading” [10], but may also require a specific interaction of SMC with ParB [17,18]. …”
Section: Introductionmentioning
confidence: 99%